2017
DOI: 10.1111/vsu.12650
|View full text |Cite
|
Sign up to set email alerts
|

Healing of canine skin incisions made with monopolar electrosurgery versus scalpel blade

Abstract: The use of monopolar electrosurgery at 10, 20, and 30 W in a cutting waveform improved hemostasis and surgical time when incising canine skin, but delayed healing and increased complications within the first 7 days compared to scalpel incisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
(162 reference statements)
1
10
0
Order By: Relevance
“…Histopathology findings were consistent with normal surgical biopsy sites and reaction to suture . Foreign body giant cell formation is considered a hallmark of foreign body reactions and was seen only around sites with suture and around necrotic adipocytes in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…Histopathology findings were consistent with normal surgical biopsy sites and reaction to suture . Foreign body giant cell formation is considered a hallmark of foreign body reactions and was seen only around sites with suture and around necrotic adipocytes in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…et al determined the effect of monopolar electrosurgery in the 10, 20 or 30 W mode for the duration of the operation, hemostasis and healing of cutaneous wounds compared to the scalpel incisions. The results of the study showed that the use of monopolar electrosurgery in different cutting regimens improved hemostasis and shortened the operation time for skin cutting in animals (15 dogs), but delayed healing and increased complications during the first 7 days compared to the scalpel incisions [13]. Ismail A. et al conducted a systematic review and metaanalysis of work comparing electrocautery cutters and surgical incisions with a scalpel [14].…”
Section: Resultsmentioning
confidence: 99%
“…No scientific works can be find in literature on comparison between electronic and cold scalpel for the excision of pilonidal disease. First report regarding the use of monopolar electrosurgery for hemostasis in human surgery has been well described since 1926 [21]. Several experimental studies on animals, demonstrated that incisions made by monopolar electrosurgery can lead to a reduction of tensile strength, delayed healing, increased infection and seroma rate and a greater areas of necrosis if compared to scalpel incision [[22], [23], [24], [25]].…”
Section: Discussionmentioning
confidence: 99%